WEB-BASED EXPERT SYSTEM FOR IDENTIFYING PESTS AND DISEASE OF OYSTER MUSHROOM - Khamidah, Ida Maratul; Putra, Emil Riza (STMIK Widya Cipta Dharma, 2022)
Oyster Mushroom is a mushroom with a circular hood like an oyster shell. Oyster mushroom cultivators must understand the art and knowledge in the cultivation of oyster mushrooms. To care for oyster mushrooms oyster mushroom cultivators usually seek knowledge through sources such as books and articles as literacy. This is unsatisfactory because it is less efficient in diagnosing diseases or pests from oyster mushrooms. Therefore, it is necessary to have an expert system that represents expert knowledge and is able to provide diagnosis and solutions from oyster pests or fungal diseases. One of the methods in the expert system is Forward Chaining. Forward Chaining is a fact to get a conclusion from that fact. In this expert system, there are 5 pests of oyster mushrooms, including mites, caterpillars, slugs, termites, rats. Oyster fungus disease in this study also has 5 types of diseases including trichoderma spp, mucor, neurospora spp, bacteria, penicillium spp. The results showed that the accuracy of the system reached 90.1%. By implementing forward chaining in the oyster mushroom expert system, oyster mushroom cultivators, especially new cultivators, can conduct consultations for the identification of oyster fungus pests and diseases effectively and efficiently. The implementation of forward chaining in the oyster mushroom expert system begins with entering the symptoms in oyster mushrooms and then processing to find out the pests or diseases that are infected. The results of the consultation are supplemented with solutions to deal with pests or diseases present in oyster mushrooms.